Avaliação de proteína quimérica recombinante mais adjuvante como candidata à vacina contra Leishmaniose Visceral - Marcelo Perdigão de Oliveira (2023)
Leishmaniasis, a neglected disease caused by parasites of the genus Leishmania, presents a variety of clinical manifestations influenced by factors such as parasite species, host genetic and immunological characteristics, as well as vectores salivary components. Disease control is challenging and currently relies primarily on interrupting the parasite's biological cycle and chemotherapy. Visceral leishmaniasis (VL) is particularly concerning, with a high mortality rate when untreated and a large number of cases reported annually, especially in regions such as Brazil, East Africa, and India. Vaccine development is considered a fundamental strategy for preventing the disease. This study focused on the construction and evaluation of a recombinant chimeric protein, ChimT, containing specific T cell epitopes from immunogenic Leishmania proteins. ChimT, associated with Th1-type immune response adjuvants, demonstrated to induce a specific Th1 immune response in murine models, characterized by high production of pro-inflammatory cytokines and IgG2a antibodies. Additionally, vaccination with ChimT resulted in a significant reduction in parasite load in the organs of infected animals. The ChimT/MPLA combination was found to be more immunogenic and protective compared to ChimT/Sap. The results suggest that ChimT has the potential as a vaccine against visceral leishmaniasis in other mammalian species, highlighting the importance of this approach for disease control.